Correlation between BMI, amount of aspirated fat and post-operative complications in VASER liposuction: A single centre experience - Giuseppe Lanzano; Filomena Napoli; Teresa Zannella; Roberta Colucci; Ida Cantiello; Giuseppe Scalera (JPRAS Open)
ABSTRACT: Background: Vibration amplification of sound energy at resonance (VASER) liposuction is an innovative technique that allows surgeons to selectively remove fat and shape desired areas of the body, resulting in more precise and controlled outcomes compared to traditional liposuction techniques. VASER liposuction offers several advantages, including targeted action that reduces trauma to the surrounding tissues, limiting pain, swelling and recovery time. Purpose: This study compared the complication rates among patients who underwent VASER liposuction in relation to their body mass index (BMI) and the amount of fat aspirated. Methods: The authors reviewed the medical records of all patients who underwent VASER liposuction at Scalera Clinic in Naples, dividing them into two groups: the first with BMI < 24.9 kg/m2 and second with BMI >25.0 kg/m2. Results: The authors examined 117 patients who were operated on within a year (2022/2023), with 48 of them having BMIs < 24.9 kg/m2 and 69 showing BMIs >25.0 kg/m2. In patients with a BMI >25 kg/m2, the most common complications were contusion, hematomas and abnormal skin retraction, whereas no complications were observed in the patients with normal-weight. Conclusions: To minimise post-operative complications and maximise results, it is advisable to select patients based on their BMI assessment, the anatomy of the treated body area and the volume of fat to be removed. This approach aims to ensure that the patients are suitable for the procedure and the achieved results align with their aesthetic expectations.